2020
DOI: 10.3390/antibiotics9080501
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Antimicrobial Susceptibility of Escherichia coli Isolates in a Taiwanese Child Cohort with Urinary Tract Infections between 2004 and 2018

Abstract: The aim of this study was to investigate the annual incidence of Escherichia coli isolates in urinary tract infections (UTIs) and the antimicrobial resistance of the third-generation cephalosporin (3GCs) to E. coli, including the factors associated with the resistance in hospitalized children in Taiwan. A large electronic database of medical records combining hospital admission and microbiological data during 2004–2018 was used to study childhood UTIs in Taiwan. Annual incidence rate ratios (IRR) of E. coli in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
3
4
0
Order By: Relevance
“…The most common gram-negative bacteria isolated from samples in our investigation was E. coli (55.0%). These findings are consistent with those of several other published studies where the prevalence of E. coli was 97.0, 92.6, 74.0, 55.0, 49.3, 43.5, 41.9, and 40.0% (Arora et al, 2016;Odoki et al, 2019;Chen et al, 2020;Daoud et al, 2020;Ali et al, 2022;Huang et al, 2022;Jagadeesan et al, 2022;Komagamine et al, 2022). In our study, 10.3389/fmicb.2022.965053…”
Section: Discussionsupporting
confidence: 94%
“…The most common gram-negative bacteria isolated from samples in our investigation was E. coli (55.0%). These findings are consistent with those of several other published studies where the prevalence of E. coli was 97.0, 92.6, 74.0, 55.0, 49.3, 43.5, 41.9, and 40.0% (Arora et al, 2016;Odoki et al, 2019;Chen et al, 2020;Daoud et al, 2020;Ali et al, 2022;Huang et al, 2022;Jagadeesan et al, 2022;Komagamine et al, 2022). In our study, 10.3389/fmicb.2022.965053…”
Section: Discussionsupporting
confidence: 94%
“…This study revealed that E. coli was the predominant uropathogen in children in our community, where the prevalence of the infected girls was higher than in boys. These findings were in agreement with the recent results obtained by several studies in Iraq, in Duhok city [ 35 ], Erbil city [ 36 , 37 ], and Baghdad city [ 38 ], as well as a Child Cohort Study in Taiwan with UTIs between 2004 and 2018 [ 39 ]. In fact, there are many factors that can affect the interpretation of UTIs in girls, particularly E. coli .…”
Section: Discussionsupporting
confidence: 93%
“…Among pregnant women, E. coli 13.5% was the most predominant bacteria and is in line with other studies in different parts of the world [25,26,27,28,29,30,31,32]. The high predominant rate of E. coli might be due to the high abundance of E. coli as fecal flora, which ascends through the genitalia to cause UTI [33].…”
Section: Discussionsupporting
confidence: 87%